2015
DOI: 10.1073/pnas.1503205112
|View full text |Cite
|
Sign up to set email alerts
|

A holistic picture of Austronesian migrations revealed by phylogeography of Pacific paper mulberry

Abstract: The peopling of Remote Oceanic islands by Austronesian speakers is a fascinating and yet contentious part of human prehistory. Linguistic, archaeological, and genetic studies have shown the complex nature of the process in which different components that helped to shape Lapita culture in Near Oceania each have their own unique history. Important evidence points to Taiwan as an Austronesian ancestral homeland with a more distant origin in South China, whereas alternative models favor South China to North Vietna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
82
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 30 publications
3
82
1
1
Order By: Relevance
“…Most of the economically important plant species introduced to Remote Oceanic islands during prehistory, such as banana, taro, breadfruit, and sugarcane, have Near Oceanic origins, whereas the sweet potato and the bottle gourd are of South American origin. Thus, the results presented by Chang et al (6), indicating that the most common variant of paper mulberry found in the Pacific, and the one most likely introduced by the early colonists, has a clear Taiwanese origin, are significant, providing (to my knowledge) the first direct genetic link between Taiwan and one of the Pacific commensal species.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Most of the economically important plant species introduced to Remote Oceanic islands during prehistory, such as banana, taro, breadfruit, and sugarcane, have Near Oceanic origins, whereas the sweet potato and the bottle gourd are of South American origin. Thus, the results presented by Chang et al (6), indicating that the most common variant of paper mulberry found in the Pacific, and the one most likely introduced by the early colonists, has a clear Taiwanese origin, are significant, providing (to my knowledge) the first direct genetic link between Taiwan and one of the Pacific commensal species.…”
mentioning
confidence: 79%
“…The haplotypes found in the north of the island, particularly cp-1, were shared with samples from the east coast region of the mainland of China, and were believed to have been introduced from there during the early phase of Austronesian expansions to the island dating between 8000 and 6000 BP (6). These northern varieties were not introduced further south, where the endemic Taiwanese lineages are found.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…(Note that maps use different temporal scales, appropriate to individual species and their temporality of spread; hatching indicates natural distribution.) papyrifera), for example, is a fiber crop introduced across the Pacific in prehistory for making barkcloth (89).…”
Section: (A) Wheat (Triticum Spp) (B) Sorghum (Sorghum Bicolor) (Cmentioning
confidence: 99%